Être musulmane dans un système scolaire dominé par des chrétiens : expériences d’élèves tanzaniennes (années 1930-années 1970) - Florence Wenzek (Revue des Mondes Musulmans et de la Méditerranée)
This article looks at the schooling experiences of Tanzanian Muslim women to analyze the contradictions in the nation-building of this East African country. Muslims and girls were minorities in the school system, and their place in the nation was ambiguous, despite the equalitarian stance of the independent state. After presenting the Tanzanian school landscape, structured by the colonial and post-colonial authorities, missionaries, and various Muslim actors, the article uses interviews and school archives to uncover pupils' experiences. It highlights the difficulties and discrimination encountered by Muslim girls in missionary but also government schools. The article also reveals significant convergences between school education and the education received by Muslim girls in their families and at the Koranic school. It concludes that, despite structural difficulties, Muslim girls, together with their families, have found a place in the process of nation-building that was occurring in schools.